Architecture of housing units in the Far North conditions - Ольга Воличенко; Сергей Огородников; Исам Ибрахим Али Абдо (Проект Байкал)
The article analyzes the factors that complicate life and construction in the extreme conditions of the Far North. For each factor, there are current methods for solving the difficulties that it provokes. Climate challenges are analyzed, and issues of logistics and autonomy of residential systems are considered. The main goal of the study is the development and adaptation of architectural solutions that take into account the specific natural conditions of the region. The article presents an experimental model of a modular residential system designed for operation in the conditions of the Far North, taking into account the derived methods of construction and operation.